ANTIPLATELET THERAPY IN PROPHILAXY OF NEGATIVE CARDIOVASCULAR EVENTS AFTER CORONARY REVASCULARIZATION. IS THERE A CONSENSUS? - Yu. I. Grinschtein; A. A. Kosinova; I. Yu. Grinschtein (Российский кардиологический журнал)
The review provides the current information about the role of antiplatelet therapy in the cardiovascular prevention in patients with coronary artery disease and coronary revascularization. Recent drugs as components of dual antiplatelet therapy after percutaneous interventions are considered. The review includes features of antiplatelet therapy after coronary bypass surgery. The paper contains points of European and American recommendations. Authors discuss the controversial and unsolved issues of antiplatelet therapy. The necessity for new dosing forms synthesis and further research for development effective prevention of adverse cardiovascular events after coronary revascularization is noted.